2,3-O-isopropylidene-L-apiono-1,4-lactone [(3S, 4S)-3,4-dihydroxy-4-(hydroxymethyl)-3,4-di-O-isopropylidene-4,5-dihydrofuran-2(3H)-one] - Best, D; Jenkinson, S; Watkin, D; Booth, K; Fleet, G (2007)
The relative configuration of the title compound, C8H 12O5, was unequivocally established by X-ray crystallographic analysis; the absolute configuration was determined by the use of D-ribose as a starting material. © 2007 International Union of Crystallography All rights reserved.